Analisis Beberapa Faktor Yang Berpengaruh Terhadap Kinerja UMKM Di Kota Surabaya - Moehammad Budi Widajanto (STIE Mandala Jember, 2019)
This study discusses aspects of government policy, socio-cultural and economic aspects, aspects of the role of related institutions; Human resource aspects, financial aspects, production and operational technical aspects, and market and marketing aspects of the performance of Micro, Small and Medium Enterprises (MSMEs) in the city of Surabaya. The analysis was carried out using descriptive and inferential using multiple linear regression analysis of 100 samples of Small and Medium Enterprises that had permits in Surabaya City. Based on the results of the study it is also known that of the seven independent variables included in multiple linear regression models, six independent variables have a positive and significant influence on the performance of MSMEs, namely aspects of government policy; aspects of the role of related institutions; Human Resource Aspects; financial aspect; production and operational technical aspects; and market and marketing aspects. While one independent variable that does not have a significant influence on the performance of MSMEs is the socio-cultural and economic aspects (X2). The results of this study also show that the independent variable of human resources (X4) has a dominant influence on the variable according to MSME Performance Performance (Y)